EVALUASI KEBIJAKAN PENANGGULANGAN NARKOBA DI INDONESIA - Ondy Asep Saputra; Jumanah; El Ainun Brilian; Ayu Nurul Khotimah; Muhammad Paridz (Journal Publicuho, 2025)
This study aims to assess drug control policies in Indonesia by concentrating on the progress of policy research, conditions of abuse, the role of rehabilitation, implementation difficulties, and government strategies. Reports from related institutions, academic publications, and national policies are secondary data sources analysed using descriptive research methods. The study shows that, although the government has launched the National Action Plan for P4GN (Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics) and increased rehabilitation as a primary strategy, there are still major problems in implementing the policy. Budget constraints, lack of coordination between institutions, overcapacity of correctional institutions, and social resistance to drugs are some of these problems. Recent data shows an increase in the number of abuse cases, especially among adolescents, where a lack of facilities and resources leads to poor rehabilitation. This study emphasises the importance of cooperation between the government, the community, and the private sector to improve the effectiveness of policies through preventive, repressive, and rehabilitative approaches. Developing new community-based programs, increasing budget allocations, and improving monitoring and evaluation systems are some of the recommendations.